Influence of social determinants of health on skin to skin contact between mother and newborn - Janaiana Lemos Uchoa; Lorena Pinheiro Barbosa; Larissa Bento de Araújo Mendonça; Francisca Elisângela Teixeira Lima; Paulo César de Almeida; Silvana Santiago da Rocha (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the association of skin-to-skin contact and social determinants of health. Methods: this is a cross-sectional study with 187 medical records of newborns from a reference rooming in in northeastern Brazil. An instrument with maternal and neonatal data was used. Analysis was descriptive and inferential statistics. For the associations, a chi-square test was used to measure strength, an Odds Ratio was calculated, with a 95% confidence interval. Results: 62% of newborns who made skin-to-skin contact at birth were eutrophic, full-term, Apgar > 7, mothers with prenatal care and without abortion. The determinants associated with non-skin-to-skin contact were preterm (CR=3.2;95%CI: 2.72-18.98); 1st minute Apgar < 7 (CR:2.9;95%CI: 2.38-3.06), cesarean section (CR:8.4;95%CI: 4.29-16.57), and unhealthy NB (CR 12.7;95%CI: 4.9-32.67). We used STROBE guidelines. Conclusion: skin-to-skin contact was influenced by gestational age, Apgar, delivery, and newborn health.